STUDI PERILAKU KONSULTAN PAJAK DALAM MENGHADAPI KENAIKAN PPN 12% TAHUN 2025: THEORY OF PLANNED BEHAVIOR - Widya Putra, Muhammad Akbar; Wanti Widodo, Ulfa Puspa (Media Mahardhika, 2025)
This study aims to understand the behavior of tax consultants in responding to the policy of increasing the Value Added Tax (VAT) rate to 12% in 2025, which is implemented alongside a new tax reporting system based on Coretax. The research employs a descriptive qualitative approach, with data collected through semi-structured interviews, participant observation, and literature review. The informants in this study consist of four tax consultants working at a Tax Consulting Office in Jombang Regency, East Java. The main theoretical framework used is the Theory of Planned Behavior (TPB), which comprises three core constructs: attitude toward the behavior, subjective norms, and perceived behavioral control. The findings indicate that tax consultants generally hold a relatively positive attitude toward the new policy, although they initially faced technical difficulties, particularly in using the Coretax system and calculating the 11/12 Tax Base (DPP). Additionally, there was external pressure from clients, colleagues, and the Directorate General of Taxes, which urged the consultants to quickly adapt. Perceived control was also relatively high, mainly due to organizational support, professional experience, and the consultants’ strong willingness to learn. This study confirms that TPB is an appropriate theoretical framework for analyzing professional behavior in the field of taxation and provides implications for policymakers to enhance training and communication aspects in every tax system reform.